2017
DOI: 10.1007/s10571-017-0482-4
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and In vitro Identification of Endocannabinoid Signaling in Periodontal Tissues and Their Potential Role in Local Pathophysiology

Abstract: The endocannabinoid system (ECS) with its binding receptors CB1 and CB2 impacts multiple pathophysiologies not only limited to neuronal psychoactivity. CB1 is assigned to cerebral neuron action, whereas CB2 is mainly expressed in different non-neuronal tissues and associated with immunosuppressive effects. Based on these tissue-selective CB receptor roles, it was the aim of this study to analyze potential expression in periodontal tissues under physiological conditions and inflammatory states. In vivo, CB rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 33 publications
6
41
0
2
Order By: Relevance
“…Recently, the EC system is suggested as an important part of the neuroimmunoendocrine response in periodontal disease [49]. Our data, as well as data of previous studies [11,14,15,18,19], suggest that the EC system influences the inflammatory response in periodontitis. Emotional stress is associated with increased salivary levels of IL-6 and IL-8 [50].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Recently, the EC system is suggested as an important part of the neuroimmunoendocrine response in periodontal disease [49]. Our data, as well as data of previous studies [11,14,15,18,19], suggest that the EC system influences the inflammatory response in periodontitis. Emotional stress is associated with increased salivary levels of IL-6 and IL-8 [50].…”
Section: Discussionsupporting
confidence: 82%
“…An involvement of the EC system in periodontitis is also suggested by studies on cannabinoid receptor expression in periodontal tissue. An in vivo study on human periodontal biopsies shows that periodontitis is associated with a decreased expression of CB1 receptor and an increased expression of CB2 receptor [11]. Another study shows an increased expression of CB1 and CB2 receptors in inflamed gingival tissue [14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that bacterial inflammation decreased CB1 expression in human periodontal ligament (PDL) cells. 19 However, it has been found that CB1 seems to be upregulated during gingival wound healing in rats. 30 To clarify the underlying role of CB1 in MSCs in mediating periodontal tissue regeneration, we explored the function and mechanism of CB1 in the osteo/dentinogenic differentiation of PDLSCs under inflammatory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have focused on the research of the ECS and its implication on immune and inflammatory diseases, including periodontal disease. [31][32][33] Most of these studies have approached this issue through cells cultures such as human gingival fibroblasts and ligament periodontal cells. 34 However, our research group reported anti-inflammatory effects on gingival tissue and osteoprotective effects on alveolar bone induced by both a CB2r and a CB1r agonist (HU308 and meth-AEA, respectively), in a model of LPS-induced periodontal disease in vivo.…”
Section: Discussionmentioning
confidence: 99%